Сыщик моей мечты: [роман] / Татьяна Полякова - Полякова Татьяна Викторовна (Авантюрный детектив, 2018)
Экземпляры: (20190716) / Инвентарный номер: / Цена: / Авт.знак: П 54 / ГРНТИ: 17.82.31 / ББК: 84(2Pос=Рус)6-44